2019
DOI: 10.33640/2405-609x.1220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incorporating Pottery and Bottom Ash as Partial Replacement of Cement

Abstract: This study addressed the environmental constraints in cement production. Ordinary Portland cement (OPC) was replaced with pottery powder (PP, produced by grinding locally available pottery) and bottom ash (BA) at 10%, 20% and 30% of cement mass. Moreover, 4% calcium chloride solution (CaCl 2 .2H 2 O) was used as mixing water. Material properties, such as standard consistency, setting time and compressive strength, were measured with different percentages of OPC replacement with PP and BA. Results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 16 publications
2
6
1
Order By: Relevance
“…Similar results were obtained by Marvila et al, 24 who evaluated the application of clay residue in mortars, replacing e 25%‐100% of hydrated lime by clay. The authors observed the same pattern of results specified by Tayeh et al 23 …”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results were obtained by Marvila et al, 24 who evaluated the application of clay residue in mortars, replacing e 25%‐100% of hydrated lime by clay. The authors observed the same pattern of results specified by Tayeh et al 23 …”
Section: Introductionsupporting
confidence: 84%
“…Similar results were obtained by Marvila et al, 24 who evaluated the application of clay residue in mortars, replacing e 25%-100% of hydrated lime by clay. The authors observed the same pattern of results specified by Tayeh et al 23 Regarding marble waste, Tayeh 25 proposed the application of several residues, including marble, the application of several residues, including marble, as a substitution for cement in percentages of 10%-30%. The author observed a drop in mechanical properties and workability, due to the removal of cement, concluding that the use of 10% of the waste is viable.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Fine aggregate was replaced by Tyre Rubber [22], Copper Slag [23] and Mica [24]. One the other hand, the cement was replaced by GGBS [14], CKD [25], Fly ash [26], rice husk ash [27] and bottom ash [28].…”
Section: Introductionmentioning
confidence: 99%